Propagation of Lime by Stem Cuttings - Swelih, Eman Ahmed; Said, Abdel Gaffar Elhag (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted during three consecutive years (2002, 2003 and 2004) to study the effects of season of the year, girdling and planting interval after girdling on rooting of stem cuttings of “Baladi” lime Citrus aurantifolia (Christm.) Swing.. Three types of stem cutting were used; namely, non-girdled and girdled apical and basal cuttings. All cuttings were collected from a single lime tree during the summer, autumn and winter seasons of each year from non-girdled and girdled branches at intervals of 2, 4, 6, 8 and 10 weeks after girdling. Cuttings were planted in sand soil in plastic trays and were kept under a plastic tent in a lath house. Cuttings planted during autumn and winter gave significantly higher percentage of rooted cuttings than the summer planted ones. Also, girdled apical cuttings gave significantly high rooting percentage compared to the girdled basal cuttings. On the other hand, no significant differences were obtained between planting intervals of 2, 4, 6, and 8 weeks after girdling, while cuttings taken 10 weeks after girdling gave significantly higher rooting percentage than the other intervals. It seems that temperature, relative humidity and the accumulative increase in quantity and quality of carbohydrates, root promoters and inhibitors play an important role, among other factors, in the rooting of lime stem cuttings.